Piramidação de genes de resistência à ferrugem asiática da soja (Phakopsora pachyrhizi Sidow) - Dias, Nicoly Aparecida Jaguszewski (2024)
Being one of the largest agricultural commodities consumed worldwide on a massive scale, Glycine max L. Merril faces the challenge of being susceptible to the currently most common pathogen for the crop, known as Soybean Asian Rust (SAR), caused by Phakopsora pachyrhizi. In efforts to mitigate problems that may hinder soybean productivity caused by P. pachyrhizi (SAR), breeding programs increasingly seek to incorporate resistance genes through molecular biology to achieve results that yield a new cultivar resistant to this pathogen. This study, through a systematic literature review conducted via a scientometric analysis, elucidates the importance of pyramiding SAR resistance genes obtained through the use of biotechnology of pyramided resistance genes (i.e., Rpps). It concludes that gene pyramiding presents na alternative for breeding programs in developing cultivars with higher levels of resistance, durability, and efficiency.